PELATIHAN PEMBUATAN PEMPEK BERBAHAN DASAR IKAN BANDENG DALAM UPAYA MENINGKATKAN USAHA MIKRO KECIL MENENGAH (UKM) PADA MASYARAKAT DESA MAUK BARAT, KABUPATEN TANGERANG. - Qadarsi, Juwita Qadarsi; Fauzi, Aziz; Laras Annisa Ulfitri Nedi; Nadia, Aisha; Wanda Yulia Utami; Muhamad Fadli; Nabila Shifa Septiani; Dewi Larasati (Universitas Islam Syekh Yusuf Tangerang, 2024)
ABSTRACT The Community Service Program (KKK) in Mauk Barat Village aims to improve the community's economy through the empowerment of the micro, small, and medium enterprises (MSMEs) sector. One of the main programs implemented is training on making pempek innovated with milkfish as the main ingredient, which is a local natural resource. This program is designed to utilize the potential of milkfish as a raw material for high-nutrition and high-market-value products, while also enhancing the community's skills in fish processing. The steps taken by the team involve three stages: Socialization, Practice & Packaging, and Marketing Education. Socialization involves raising awareness of the importance of entrepreneurship to improve the economy. Practice & Packaging includes training on making pempek from milkfish and packaging it into a highly marketable product. Marketing education teaches how to sell both online and offline. The training is conducted using a participatory method, actively involving the community in every stage, from planning to implementation. As a result of the training, participants successfully applied the skills they acquired in independently producing milkfish pempek, guided by experienced instructors, and the community began to develop home-based businesses, which led to increased economic income. This program contributes to improving the village economy through the development of MSMEs based on local potential.